Developing executive talent : a practical guide - Farnsworth, Terry (London ; New York : McGraw-Hill, 1975)
The book provide practical guidance to all executives who wish to become more effective developers of people and to develop themselves through better self-management. It deals with those practical problems of training and self-development which all too often are glossed over in the literature and yet which frequently inhibit effective action.
Includes index.
Includes bibliographical references: p.157-158.
ne 13/07/2018
Loans
Keywords: Executives; Executive ability; United Kingdom